Detection of Clostridium difficile toxins A and B from Antibiotic- Associated Diarrhea and Colitis in Iraqi children, by ELISA Test: Mona Turkey AL-Mossawei and Luma Yousif Mahdi - Mahdi, Luma Yousif (The Iraqi Journal of Veterinary Medicine, 2015)
This study focuses on diagnosis of Clostridium difficile causing Antibiotic – Associated diarrhea and colitis by Elisa method and to detect of C. difficile Toxin A and B in stool samples by Elisa test. Two hundred forty (240) stool samples were collected from children suffering from antibiotic- associated diarrhea and Colitis cases at ages from after birth to 15 years old from Baghdad hospitals. Samples were taken during the period of first of June 2013 until the end of April 2014. In addition to that 80 samples from healthy children of the same age and sex as a control group. Clostridium difficile Toxin A and B in stool samples were detected. Results of this study indicated that females were more infected than males. Overall positivity was 21.25% in present studied group compared to controls (P<0.05). In conclusion, the majority percent from age <1year 15% and this percent decreased with the advance in age.